Perencanan Ulang Transmisi Daya Mekanik Mesin Penghancur Es Balok Di Pasar Bina UsahaKota Meulaboh - T Azwar; Pribadyo Pribadyo (Jurnal Mekanova: Mekanikal, Inovasi dan Teknologi, 2015)
The process of ice crusher bars in the shredder ice used in the fish market building efforts in Meulaboh is not optimal anymore work given that there are parts of the engine components that are no good in this case can also be seen from at least the production of ice produced at less than 24 kg / min, and based on the observations of the author of the engine sound is also louder and the machine is not standard anymore. Starting from the problem, the purpose of this planning the authors feel the need to plan the re-shredder ice blocks into better and more efficient work. in general usually machine consists of three main parts that work. Wherein the third part is the driver, the successor system power (power transmission) and the driven part. The initial step in planning is to conduct market surveys of business building in the city of Meulaboh. The next step is to plan and calculate the component elements of the machine, planning and calculation performed on the shaft, pulley-belt and bearing on tools that have been designed. The final step in the planning process is made by evaluating the results of calculations performed. Obtained from the calculation of the production capacity amounted to 33, 411 kg / minute appropriate. Keywords: ice crusher machine, shafts, belts, pulleys, bearings